Police Cooperation and the Fight Against Cross-Border Crime along Belt and Road Countries: The Emergence and Proliferation of Telecomm unication Fraud in Greater China (The Macau Ricci Institute Journal, 2019)
Instances of telecommunication fraud in the region of Greater China – the Peoples Republic of China (PRC), Hong Kong, Macao and Taiwan – have increased since 2015. Some criminal elements involved in telecommunication fraud have been operating in Belt and Road countries outside either the PRC or Taiwan. The governments of Greater China have been cooperating to combat telecommunication fraud. This paper examines the pattern of telecommunication fraud and addresses the issue of how the governments of China and Taiwan have been tackling it in cooperation with the countries involved in the Belt and Road Initiative (BRI).